Capital Structure of Bugo Jepara Village Bakery Industry Center...? Sales Growth and Profitability - Rusdianto, Hutomo; Andriani, Evana; Syafira, Wafda Rahimatus (Global Health Science Group, 2023)
The study aims to determine sales growth and profitability of the capital structure for the bakery industry in Bugo Village as an Industrial Center. The research design uses quantitative descriptive research using skunder data taken directly from respondents in the form of sales reports and financial statements. The population and sample are owners or decision makers in the bakery industry totaling 24 respondents. The results of the study explained that profitability was not able to improve the capital structure for MSMEs in Bugo Village, but sales growth was able to improve the capital structure. This is because most MSMEs in Bugo Village have been in business for a long time and are carried out consistently, dare to compete and always prioritize the ability to increase sales by innovating. Research findings turn out that the need to innovate is very important in order to survive in the global era.